Training on Financial Management and Budget Planning for the Sustainability of MSMEs - Asiah, Neng; Sabaruddinsah, Sabaruddinsah; Wulandari, Dian Sulistyorini; Devarianti, Yusnia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program aimed to enhance the financial management and budget planning capabilities of Micro, Small, and Medium Enterprises (MSMEs) in the stationery and office supply sector in Cikarang Pusat. The program was conducted over two weeks from August 12 to August 26, 2024, with weekly training sessions held at the business locations of the participants. A total of eight MSME owners actively participated in the training, which focused on key financial management concepts such as cash flow management, expense tracking, and profit analysis. The program utilized a combination of theoretical presentations and practical workshops to ensure the immediate application of the learned skills. The results of the program were highly positive, with significant improvements observed in participants' financial literacy and practical skills. Financial literacy increased from 25% to 87.5%, the ability to create a budget rose from 12.5% to 87.5%, and 75% of participants successfully implemented effective cash flow management practices. The findings underscore the importance of targeted, hands-on training in improving MSMEs' financial practices and supporting their sustainability.